2018
DOI: 10.1289/ehp1955
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Mancozeb Exposure, Excess Manganese, and Neurodevelopment at 1 Year of Age in the Infants’ Environmental Health (ISA) Study

Abstract: Background:Although growing evidence suggests that early-life excess manganese (Mn) impairs neurodevelopment, data on the neurodevelopmental effects of mancozeb, a fungicide containing Mn, and its main metabolite ethylenethiourea (ETU) are limited.Objective:We examined whether prenatal mancozeb exposure and excess Mn were associated with neurodevelopment in 355 1-y-old infants living near banana plantations with frequent aerial mancozeb spraying in Costa Rica.Methods:We measured urinary ETU, hair Mn, and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 61 publications
(85 reference statements)
0
27
0
3
Order By: Relevance
“…In children under 6 years of age, evidence from cohort studies in Table 1 revealed that higher manganese exposure had a negative effect on neurodevelopment [29][30][31][32][33][34][35][36], mainly cognitive and motor development. These studies enrolled pregnant women and mainly collected biomarker tissues, such as cord blood, maternal blood and hair, as well as placenta at delivery [29,30,32,[34][35][36].…”
Section: Manganese In Biomarkers and Neurodevelopmental Outcomesmentioning
confidence: 99%
“…In children under 6 years of age, evidence from cohort studies in Table 1 revealed that higher manganese exposure had a negative effect on neurodevelopment [29][30][31][32][33][34][35][36], mainly cognitive and motor development. These studies enrolled pregnant women and mainly collected biomarker tissues, such as cord blood, maternal blood and hair, as well as placenta at delivery [29,30,32,[34][35][36].…”
Section: Manganese In Biomarkers and Neurodevelopmental Outcomesmentioning
confidence: 99%
“…Our results show linear associations with all the cognitive and psychomotor scales. Similarly, studies using chronic exposure measures (hair or dentine Mn levels) also indicate a linear association between prenatal Mn and long-term cognitive outcomes [15,49]. Gunier et al [14] described a linear association with cognitive development but a non-linear association with psychomotor development, while other authors proposed an inverted U-shape association between maternal blood Mn and neurodevelopment [1] and some studies have suggested that there may be a threshold value above which there is an association with neurodevelopment [1,31].…”
Section: Discussionmentioning
confidence: 96%
“…A sensitive segment of the population, exposed to mancozeb, is represented by pregnant women, who use agricultural products and are at risk from their side effects. In this context, mancozeb crosses the blood-placenta [48,51,52] and the blood-milk barriers [53], compromising the development of offspring, from intrauterine to postnatal life [54].…”
Section: Discussionmentioning
confidence: 99%